Assessing the quality of care in primary health care facilities in all municipalities in Kosovo 2016–2023 - Astrid M. Knoblauch; Astrid M. Knoblauch; Sarah Rajkumar; Sarah Rajkumar; Robert Canavan; Robert Canavan; Qamile Ramadani; Ariana Bytyçi Katanolli; Shegë Bahtiri; Debra Stevenson; Debra Stevenson; Debra Stevenson; et al. (Frontiers in Public Health)
IntroductionAccess to quality primary healthcare (PHC) in Kosovo is progressive with substantial reforms that have been implemented to promote the health of its people since its independence in 2008. However, substantial challenges remain, particularly among managing non-communicable diseases (NCD) like diabetes and hypertension, due to gaps in structural and procedural aspects. The Accessible Quality Healthcare project (2016–2027) aimed at improving the health of the Kosovar population by strengthening the quality of PHC services with a specific focus on NCDs. Three quality of care studies were conducted with the aim of measuring progress in PHC and NCD management.MethodsThree facility-based, cross-sectional studies were conducted in 2016, 2018 and 2023 across 12, 20, and 38 selected municipalities in Kosovo, respectively. Data were collected on PHC infrastructure, provider-patient interactions, and patient outcomes using standardized assessments, observational tools, and exit interviews.ResultsThe overall infrastructure score improved from 56% in 2016 to 68% in 2023. Clinical observation scores comprised five categories. For instance, doctors’ knowledge and compliance with clinical history and physical examinations revealed a marked increase overall from 2016 to 2023, hygiene and infection prevention control measures increased steadily in 14 municipalities but remained below 60% in 16 municipalities. Clinical adherence to guidelines for managing diabetes and hypertension improved markedly but remained low overall (from 36% in 2016 to 60% in 2023 with regards to diabetes and 35% in 2016 to 58% in 2023 regarding hypertension). The overall experience of patients exiting facilities was positive and their perception of doctors’ behaviour scored more than 60% in all years and in seven of the eight indicators. Negative exceptions included a drop in explanations regarding medicine intake from 96% in 2016 to 56% in 2023 and regarding the doctors’ verbal anamnesis, physical examination and explaining the health problems (from 97% in 2016 to 77% in 2023).ConclusionWhile marked progress was made in improving Kosovo’s healthcare infrastructure and clinical practices, persistent disparities in municipal performance and gaps in doctor-patient communication highlight the need for targeted interventions. Continued investment in healthcare worker training, better adherence to clinical protocols, and improved communication will be essential to sustain progress and align Kosovo’s healthcare system with European Union standards.